2016
DOI: 10.1016/j.apmr.2016.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular Impairments Contributing to Persistently Poor and Declining Lower-Extremity Mobility Among Older Adults: New Findings Informing Geriatric Rehabilitation

Abstract: Objective To identify neuromuscular impairments most predictive of unfavorable mobility outcomes in late-life. Design Longitudinal cohort study. Setting Research clinic. Participants Community-dwelling primary care patients aged ≥65 years (N=391) with self-reported mobility modifications, randomly selected from a research registry. Intervention(s) Not applicable. Main Outcome Measure(s) Categories of decline in and persistently poor mobility across baseline, 1 and 2 years of follow-up in the Lower-Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 36 publications
1
40
0
Order By: Relevance
“…Similarly, Straight and colleagues (2016) demonstrated that leg extension power asymmetry was weakly correlated to 6-minute walk, timed up-and-go, and 30-s chair stand tests and was an independent predictor of overall lower-extremity function only after controlling for total leg power, age, comorbidities, physical activity and adiposity. Longitudinal data from the Boston RISE study demonstrated that weaker leg strength was associated with a nearly two-fold likelihood of declining lower-extremity function, yet strength asymmetry was not (Ward, Beauchamp et al 2016). Taken together, these results suggest that the asymmetry of strength and power is only marginally related to the functional mobility of older adults.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, Straight and colleagues (2016) demonstrated that leg extension power asymmetry was weakly correlated to 6-minute walk, timed up-and-go, and 30-s chair stand tests and was an independent predictor of overall lower-extremity function only after controlling for total leg power, age, comorbidities, physical activity and adiposity. Longitudinal data from the Boston RISE study demonstrated that weaker leg strength was associated with a nearly two-fold likelihood of declining lower-extremity function, yet strength asymmetry was not (Ward, Beauchamp et al 2016). Taken together, these results suggest that the asymmetry of strength and power is only marginally related to the functional mobility of older adults.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that previous investigations of strength and power asymmetry in older adults have used a range of testing modalities including pneumatic resistance, the Nottingham Power Rig, and isokinetic dynamometry, and, some studies measured knee extensor asymmetry whereas others measured whole-leg asymmetry (Skelton, Kennedy et al 2002, Portegijs, Sipila et al 2005, Perry, Carville et al 2007, Carabello, Reid et al 2010, LaRoche, Cook et al 2012, Bean, Latham et al 2013, Straight, Brady et al 2016, Ward, Beauchamp et al 2016). These studies are therefore not directly comparable because of the task-specificity of asymmetry and the use of compensatory mechanisms that may mask single-joint strength and power asymmetries during whole-leg exercises (Bond, Cook et al 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studying the neuromuscular functional decline of the lumbar back extensors muscles would be particularly promising, because these muscles have a higher than average rate of muscle loss with 2.5% per year [19]. In addition, poor back extension strength and endurance was found to be predictive of future falls, impaired mobility, frailty, and the need for institutionalization in older adults [20][21][22][23]. Recent observations by this research group found the surface electromyographic (SEMG) based measures of back muscle fatigue capable of identifying early agedependent changes in individuals who did not demonstrate a major back strength decline with aging [24].…”
Section: Introductionmentioning
confidence: 99%
“…In a recently published clinical demonstration project evaluating a rehabilitative care program addressing mobility problems under Medicare reimbursement guidelines, robust improvements in mobility were observed even after accounting for health factors that might impede progress such as pain or cognitive impairment. This program targeted specific neuromuscular impairments identified as relevant to mobility and focused on other important elements such as principles of behavioral change [ 5 – 7 ]. However, limitations with program engagement and retention of patients were observed due to the frequency of outpatient visits required (average 10–12) and transportation limitations given that these patients manifested mobility limitations.…”
Section: Introductionmentioning
confidence: 99%